PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA KELAS III SDN SUKARAJA II PADA MATERI PELESTARIAN LINGKUNGAN - Wiwin, Wiwin; Sujana, Atep; Julia, Julia (Jurnal Pena Ilmiah, 2017)
Creative thinking skills need to be applied to students, both in the home, school, and community. One way that can be done to develop and improve creative thinking skills is to apply problem-based learning. This study aimed to find out the improvement and difference in the improvement of creative thinking skill in high, medium, and low group students after being treated in the form of problem based learning. The method in this research is pre-experimental method with one-group pretest-posttest design. The samples are students grade III SDN Sukaraja II. Instruments used in this study is test and non-test. The results of this study showed that of the Paired sample t-test of the three groups and one-way anova had P-value of 0.000, this means there is a significant increase and difference in the increase in the creative thinking skills of high, medium, and low group students.Â